Deleites de la cocina Mexicana = Healthy Mexican American cooking - Urdaneta, María Luisa, 1931- (University of Texas Press, 1996)
Mexican food, Tex-Mex, Southwestern cuisine--call it what you will, the foods that originated in Mexico have become everyone's favorites. Yet as we dig into nachos and enchiladas, many people worry about the fats and calories that traditional Mexican food contains. This book proves that Mexican cooking can be both delicious and healthy. This bilingual cookbook provides over 200 recipes for some of the most popular Mexican dishes. Without sacrificing flavor, the authors have modified the recipes to increase complex carbohydrates and total dietary fiber, while decreasing saturated and total fats. These modifications make the recipes suitable for people with diabetes--and all those who want to reduce the fats and calories in their diet. Each recipe also includes a nutritional analysis of calories, fats, sodium, etc., and American Diabetic Association exchange rates.--From publisher description.